Finite element modelling to predict hardness of Mg alloy reinforced with Ti/Hydroxyapatite hybrid composites – An axisymmetric approach. (2022) - Vignesh, P.; Ramanathan, S.; Ramesh, K.; Joseph Arockiam, A.
Abstract: Magnesium based MMCs are widely investigated for orthopaedic applications because of its degradable property. In order to reduce the experimental trials on designing these composites that mimic the natural human bone, Finite element method has been widely employed. This work analyses finite element model of Mg-3Zn alloy matrix reinforced with micron sized 1% Ti particles/ 1.5 % hydroxyapatite particles (hybrid reinforcements) to predict hardness indentation load displacement curves as these composites can be used as load bearing support for fractured bone. Local mechanical responses measured by indentation technique by local measurements are correlated. Stiffness response of the composite to indentation sensitivity is analysed with constitutive parameters. Relations between influence of reinforcements and the material property to aid experimentation are addressed. Critical differences and similarities in strain fields shape, magnitude and size are established. It was observed that the experimental hardness results of the composites are in good agreement with the simulated results.